A falcon shrine at the port of Berenike (Red Sea coast, Egypt) - Oller Guzmán, Joan; Abella, David Fernández; Pita, Vanesa Trevín; Kaper, Olaf E.; Ast, Rodney; Osypińska, Marta; Sidebotham, Steven E. (American journal of archaeology, 2022)
During excavations at the Hellenistic-Roman port of Berenike (on the Red Sea coast of Egypt) in the winter of 2019, work in the so-called Northern Complex documented a religious space from the Late Roman period. The excavation of a portion of this space recorded material that, together with the architecture, suggests a ritual function associated with a falcon cult. This study examines the features of this edifice and the interpretation of the religious materials found in it and proposes a possible relationship with the Blemmyan population who lived in Berenike between the fourth and sixth centuries CE.1
Gesehen am 04.10.2023